Study on the optical rectification and second-harmonic generation with position-dependent mass in a quantum well. (August 2018) - Yu, Qiucheng; Guo, Kangxian; Hu, Meilin; Zhang, Zhongmin; Li, Keyin; Liu, Dongfeng
Abstract: In this paper, the energy levels and the wave functions of the schrödinger equation with position-dependent mass (PDM) are theoretically deduced, and they are brought into the nonlinear optical rectification (OR) and the second harmonic generation (SHG). We find that the peaks of coefficient curves of optical rectification and second harmonic generation become larger and occur blue shift under the condition of variable mass. Moreover, with the increment of mass variable k, the energy interval E i j decreases, which makes the coefficients suffer a red shift, and the absolute value of the matrix elements product | M i j M j k M k i | presents different monotonicity, that makes the peaks value of coefficients change regularly. Highlights: This paper mainly explores the different characteristics in nonlinear optical rectification and the second harmonic generation that leading into the special energy levels and wave functions of schrödinger equation with PDM. With the effect of PDM, the matrix elements Mij grow, which lead to the peak values of the OR coefficient and SHG coefficient become larger. Moreover, because of the increment of the energy intervals E21and E31, the coefficients curves appear in the larger incident photon energy region that called a blue shift. With the increase of the mass variable k, the energy intervals of optical rectification and second harmonic generation decrease, which makes the coefficients curves appear red-shift phenomenon. The absolute value of the matrix elements product .|MijMjkMki| presents different monotonicity, that makes the peaks value of coefficients change regularly.